2012
DOI: 10.1007/s10853-012-6583-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of straight multi-walled carbon nanotubes by arc discharge in air and their field emission properties

Abstract: The possibility of preparing straight multiwalled carbon nanotubes (MWCNTs) on a large scale is demonstrated using direct current arc discharge with a rotating graphite anode in low pressure air. The process is time-saving, economical, and non-hazardous. It is found that the optimum air pressure for the highest yield of MWCNTs is about 60 Torr. Investigation of the internal organization of the cathode deposit reveals that many columns about 40 lm in diameter are closely packed and mechanically stable. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…However, the high air pressure in the arc chamber easily results in a unstable plasma in the arc discharge process due to the violent reaction between excessive O 2 and graphite electrode. Zhao et al [54] investigated systematically the synthesis of MWCNTs using DC arc discharge with a rotating graphite anode in low-pressure air. It is found that the optimum air pressure for the highest yield of MWCNTs is about 60 Torr.…”
Section: Experimental Results Show That the Inner Diameter And The Lementioning
confidence: 99%
“…However, the high air pressure in the arc chamber easily results in a unstable plasma in the arc discharge process due to the violent reaction between excessive O 2 and graphite electrode. Zhao et al [54] investigated systematically the synthesis of MWCNTs using DC arc discharge with a rotating graphite anode in low-pressure air. It is found that the optimum air pressure for the highest yield of MWCNTs is about 60 Torr.…”
Section: Experimental Results Show That the Inner Diameter And The Lementioning
confidence: 99%
“…The hybrid architecture materials of MWCNTs and graphitic platelets were prepared in a sealed chamber using DC arc discharge method following the process described in our previous work [9,10]. The cylindrical deposit was firstly cut into a slice with a thickness of~1 mm as anode material and then simply heated at 750°C for 30 min in air.…”
Section: Methodsmentioning
confidence: 99%
“…The field enhancement factor of CCNSs is 27000, calculated from the slope of the F-N plot by assuming the work function of CNTs as 5.0 eV [12]. Some groups have reported previously the field enhancement factors of CNT-based emitters such as a self-standing CNT fiber [21], vertically aligned CNT arrays on graphene layers [22], few-layer graphene on CNTs [23], and straight multi-walled CNTs [24] as 65000, 5340, 3980, and 7830, respectively. On the comparison of CCNS and other CNT-based emitters, the value for CCNS is between that of a CNT fiber and graphene.…”
Section: Electron Emission Property Of Electron Gunmentioning
confidence: 99%